Seasonal dynamics of cereal aphid population - Fedorenko, A. (Quarantine and plant protection, 2024)
Goal. To compare the seasonal dynamics of cereal aphid abundance in the Steppe and Forest-Steppe zones during 2023 and to determine the factors that influenced it. Methods. To assess the state of the cereal aphid population on cereal crops, we used the results of personally conducted entomological phytosanitary monitoring of crops (according to generally accepted methods) in the farms of the Steppe and Forest-Steppe zones; information from current reports from the places where field experiments were conducted directly by the forecasting laboratory, as well as other laboratories of the IPP of NAAS, which is also confirmed by the materials of decadal reports of regional plant protection stations and signalization and forecasting points of the State Inspection of Plant Protection, confirmed by information on the phytosanitary status of regional state research stations. Cereal aphid adults and larvae were counted in populations of populations (in the crop phase, the end of the tube emergence is earing). Results. The state of cereal aphid populations on crops of cereal spiked crops in 2023 was studied, both in general in Ukraine and separately in the Steppe and Forest-Steppe zones. The dynamics of their number in farms of different natural and climatic zones was investigated, and an analysis of its peculiarities in the conditions of the year was carried out. Conclusions. In 2023, the harmfulness of cereal aphids on cereal crops remained at the level of long-term averages. The expansion of their harmful zone and an increase in their number was noted during the earing period (milk ripeness). On winter cereal crops, phytophages prevailed in the Steppe zone. In the Forest-Steppe zone, the phytophage was more damaging to winter cereals than to spring cereals. The results of entomological monitoring in Mykolaiv region (State Enterprise «Experimental Farming «Zori nad Bugom») showed that during the accounting period the bulk of aphids were concentrated on winter wheat crops, and winter barley was damaged in small numbers. On the contrary, the surveys conducted in Kyiv region (State Enterprise «Experimental Farming «Salyvonkivske») showed that in the second half of June — the first decade of July, the number of aphids on spring barley crops was approximately twice as high as on spring wheat. As a result of the study, it was practically confirmed that the optimal temperature regime for the development of cereal aphids is 16—20°C, and the relative humidity is 60—80%.